2010
DOI: 10.1152/ajpheart.00293.2010
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Ca2+ sparks and Ca2+ homeostasis in a minimal model of permeabilized ventricular myocytes

Abstract: ] in the myoplasm or SR can influence the frequency, amplitude, and kinetics of local events. In ventricular myocytes, for instance, propagating Ca 2ϩ waves emerge when spontaneous Ca 2ϩ sparks trigger additional sparks in a regenerative fashion (5). Similarly, changes in channel gating at the level of individual RyRs can immediately affect the production of local events and, over time, influence bulk myoplasmic and SR [Ca 2ϩ ]. An increase in RyR opening will cause a gradual decrease in SR [Ca 2ϩ ] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Williams et al demonstrated that a population of subspace domains can be represented by a probability density approach and can be utilized to simulate global calcium dynamics [45]. Hartman et al utilized a model of a small number of coupled calcium activated channels to predict the global calcium release dynamics in response to pharmacological modification of single channel kinetics [46]. However, this study is the first to compare a model of calcium channel regulation accounting for the finite subspace volume (and using a discrete representation of the number of subspace calcium ions) with the corresponding ODE formulation that assumes a large system size (and uses a continuous representation of calcium concentration).…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al demonstrated that a population of subspace domains can be represented by a probability density approach and can be utilized to simulate global calcium dynamics [45]. Hartman et al utilized a model of a small number of coupled calcium activated channels to predict the global calcium release dynamics in response to pharmacological modification of single channel kinetics [46]. However, this study is the first to compare a model of calcium channel regulation accounting for the finite subspace volume (and using a discrete representation of the number of subspace calcium ions) with the corresponding ODE formulation that assumes a large system size (and uses a continuous representation of calcium concentration).…”
Section: Discussionmentioning
confidence: 99%
“…S3 qualified as Ca sparks). As the detection threshold increases, nonspark leak is increased (25). If we reduce our detection threshold to D[Ca] I ¼ 0.05 mM, more Ca sparks are seen ( Fig.…”
Section: Methodsmentioning
confidence: 95%
“…The first study to simulate both stochastic spark triggering and cellular action potentials (APs) was published by Greenstein and Winslow in 2002 [62]. Several studies published more recently have used either elegant algorithms [63-68], or improvements in computational power [69-74], to develop new models. The biological questions that can be asked with these models, however, are somewhat different from those that can be addressed with the lumped models.…”
Section: A Review Of Recent and Historically-important Studiesmentioning
confidence: 99%
“…In these newer models, however, SR Ca 2+ leak via stochastic gating of RyRs is simulated explicitly. Several studies published in the past few years have computed leak in a resting myocyte as a function of SR [Ca 2+ ] and have used the simulations to quantify the relative importance of visible leak in the form of Ca 2+ sparks, versus “invisible” leak that would be difficult to detect with standard recording techniques [68, 70, 73, 74]. Sensitivity analyses with these newer models can therefore consider additional model outputs, such as the resting spark rate or the number of Ca 2+ sparks triggered by specific voltage-clamp depolarizations.…”
Section: A Review Of Recent and Historically-important Studiesmentioning
confidence: 99%